1994
DOI: 10.1093/jaoac/77.2.541
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Problems in Recovery of Fumonisins Added to Corn-Based Foods

Abstract: Because the natural occurrence of fumonisins is so far known almost exclusively in corn, we have limited our investigations on their stability to corn-based foods. In these studies, distinction must be made between real losses, binding, and any matrix-related method problems. Fumonisins B1 (FB1) and B2 (FB2) were about 40% recovered when heated in corn meal at 190°C, about 20–30% recovered when heated in moist corn meal at 190°C, and completely unstable in corn meal at 220°C. Average recoveries of FB1 and FB2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
3
4

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 0 publications
6
41
3
4
Order By: Relevance
“…Dupuy et al (1993), however, reported a 50% reduction in FB 1 levels when dry contaminated corn culture material was heated for 10, 30, and 175 min, and 8 hr at 150, 125, 100, and 75°C, respectively. Scott and Lawrence (1994) reported that FB 1 , when heated at 190°C for 60 min, was ≈20% recovered in dry corn meal and ≈42% recovered in moist corn meal. No FB 1 was found after heating the corn meal at 220°C for 25 min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dupuy et al (1993), however, reported a 50% reduction in FB 1 levels when dry contaminated corn culture material was heated for 10, 30, and 175 min, and 8 hr at 150, 125, 100, and 75°C, respectively. Scott and Lawrence (1994) reported that FB 1 , when heated at 190°C for 60 min, was ≈20% recovered in dry corn meal and ≈42% recovered in moist corn meal. No FB 1 was found after heating the corn meal at 220°C for 25 min.…”
Section: Resultsmentioning
confidence: 99%
“…Still, these reductions also may be a result of true degradation or increased binding to the matrix during the extrusion cooking process. Differentiation of real losses from problems related to the food matrix is very important (Scott and Lawrence 1994). Nixtamalization of F. proliferatumcultured corn resulted in the hydrolysis of FB 1 to hydrolyzed FB 1 (HFB 1 ), but HFB 1 was still toxic when fed to rats (Hendrich et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also shown that the extraction efficiency of fumonisins decreased when 70:30 MeOH:water was used as the extraction solvent (Jackson, 1997;Scott and Lawrence, 1994). The ELISA method used 70:30 MeOH:water as extraction solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Also >80% of FB 1 and FB 2 were lost at temperatures Ն175°C for 60 min. In another study, FB 1 and FB 2 were reduced by about 60% when heated in corn meal at 190°C for 60 min, by about 70-80% when heated in moist corn meal at 190°C for 60 min, and about 100% in corn meal at 220°C for 25 min (Scott and Lawrence, 1994).…”
Section: Hplcmentioning
confidence: 90%
“…1992. Methods of decontamination ; Of the six fumonisins known, only fumonisins B1, B2 and Park et al 1992) and destruction by heat (Dupuy et al 1993;B3 (FB1, FB2, FB3) are produced in substantial amounts by Scott and Lawrence 1994) have not yet proved fully satiscultured F. moniliforme (Cawood et al 1991). Since their factory.…”
Section: Introductionmentioning
confidence: 99%